2021
DOI: 10.1186/s12913-021-06505-1
|View full text |Cite
|
Sign up to set email alerts
|

Fostering innovative behavior in health organizations: a PLS-SEM analysis of Norwegian hospital employees

Abstract: Background Health organization research is experiencing a strong refocus on employees’ individual innovative behavior (IIB), revealing that many of the influential factors at work remain uncertain. Hence, this study empirically examines fostering of hospital employees’ IIB by focusing on direct and indirect relationships of organizational culture (here labeled internal market-oriented culture, IMOC), psychological capital (PsyCap), and organizational commitment (OC). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 96 publications
0
17
0
1
Order By: Relevance
“…services [1], with improvements in areas such as value, efficiency, and innovative thinking [1][2][3]. Increased patient needs and demand for care are pushing health organizations to keep pace with the increasingly challenging health industry and the complexity of offering quality healthcare [1,4].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…services [1], with improvements in areas such as value, efficiency, and innovative thinking [1][2][3]. Increased patient needs and demand for care are pushing health organizations to keep pace with the increasingly challenging health industry and the complexity of offering quality healthcare [1,4].…”
mentioning
confidence: 99%
“…services [1], with improvements in areas such as value, efficiency, and innovative thinking [1][2][3]. Increased patient needs and demand for care are pushing health organizations to keep pace with the increasingly challenging health industry and the complexity of offering quality healthcare [1,4]. Employee innovativeness is not only becoming essential for addressing patient needs and demands [5], but also indispensable for a continued expansion and adoption of novel ideas in response to current environmental and market changes [6,7].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…(Zhou and Shalley, 2003;Zhang and Bartol, 2010;Qiu et al2015). Employees depicting high innovative behaviour help organizations to out-perform in the constantly changing business environment (Mutonyi et al, 2021). Studies have found that creative and innovative employee behaviour is linked to better quality of services, higher customer satisfaction as well as better performance (Sanders et al, 2010).…”
Section: Introductionmentioning
confidence: 99%